Animals as objects and subjects of ecological criminal and misdemeanour law, with special reference to the dog - Vari, Vince (Glasnik Advokatske komore Vojvodine, 2024)
The protection of animals plays a crucial role in the legal system related to environmental protection. Act C of 2012, effective from July 1, 2013, includes a dedicated chapter on protecting the environment, wildlife, and their elements. Hungarian regulations on environmental liability encompass civil, administrative, misdemeanor, and criminal liability. In this paper, I aim to present the fundamental legal aspects of protecting animals within environmental law. I will focus on legislation and practical issues falling under infringement law, particularly concerning dogs. Environmental law regarding dogs is two-fold. Firstly, it protects animals from abusive behavior, whether physical or mental. Secondly, it involves situations where dogs become a part of environmental law, such as when they are released into public areas without proper supervision. The clear delineation of specific acts poses a challenge for law enforcement, emphasizing the need to clarify the legislative environment and its practical aspects
Keywords: animal protection, environmental protection, liability for violation of rules, danger with a dog, animal cruelty